Cutaneous Mucormycosis Complicating a Polymicrobial Wound Infection Following a Dog Bite. (23rd June 2011) - Zachary, Dalila; Chapin, Kimberly; Binns, Linda; Tashima, Karen
Abstract : We report a case of cutaneous mucormycosis and Enterobacter infection developing in a 50-year-old diabetic woman following a dog bite that showed delayed development and diagnosis in comparison with typical zygomycotic cutaneous lesions.